PEDAGOGICAL VIEWS OF NASIRIDDIN TUSI - Matyakubova, (EPRA International Journal of Multidisciplinary Research (IJMR), 2023)
Nasiriddin Tusi was a prolific author whose works are yet to be fully explored by researchers. His writings can be found in museums and libraries across the world including in Baku, Paris, Berlin, Vienna, Oxford, Cambridge, Leipzig, Munich, Florence, Cairo, Istanbul, Moscow, St. Petersburg, and Kazan. One of Tusi’s most notable works, “Akhloqi-Nasiri” was the first systematic moral book in the Islamic world. Written in Persian, this work is still relevant today as it addresses issues that are timeless.